Penyelesaian Sengketa pada Perjanjian Pembelian Tenaga Listrik melalui Arbitrase - Anton Wahjosoedibjo (BANI Arbitration and Law Journal, 2025)
ABSTRACT The purchase of electrical power by an off-taker from an Independent Power Producers (IPP) is administered by a Power Purchase Agreement (PPA). After a power project developer secured the power generation project through tender process or direct appointment, the project developer sets a special project company with its sponsor to build, own and operate the power plant for a specific term, and sign a PPA with the off-taker to administer the power sales. In Indonesia the off-taker for public utility is PT PLN (Persero). Each PPA is specific for a certain power project. However, there are a model PPA for each type of power generation project which addressed specific topics agreed upon by both parties in the PPA, that are formulated in the heads of agreement. These are sources of disputes in implementing the PPA. If the dispute cannot be resolved through amicable discussions between the two parties, then they bring the case for settlement in the court or arbitration tribunal. This paper discusses common disputed issues in a PPA and offers alternative solutions through arbitration tribunals.